2020
DOI: 10.1007/s11684-020-0812-7
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-targeted cancer therapy: great target but disappointing clinical outcomes, why?

Abstract: The mammalian target of rapamycin (mTOR) critically regulates several essential biological functions, such as cell growth, metabolism, survival, and immune response by forming two important complexes, namely, mTOR complex 1 (mTORC1) and complex 2 (mTORC2). mTOR signaling is often dysregulated in cancers and has been considered an attractive cancer therapeutic target. Great efforts have been made to develop efficacious mTOR inhibitors, particularly mTOR kinase inhibitors, which suppress mTORC1 and mTORC2; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 98 publications
(145 reference statements)
1
30
0
Order By: Relevance
“…It is reported that targeting mTOR activates the mediators involved in the PI3K or other signaling pathways. 45,46 For example, rapalogs increase AKT phosphorylation while suppressing mTORC1 function. Moreover, mTOR inhibition is reported to activate MAPK/ERK signaling in cancer cells.…”
Section: Mirna and Leukemiasmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that targeting mTOR activates the mediators involved in the PI3K or other signaling pathways. 45,46 For example, rapalogs increase AKT phosphorylation while suppressing mTORC1 function. Moreover, mTOR inhibition is reported to activate MAPK/ERK signaling in cancer cells.…”
Section: Mirna and Leukemiasmentioning
confidence: 99%
“…There are several reasons for failure of these drugs. It is reported that targeting mTOR activates the mediators involved in the PI3K or other signaling pathways 45,46 . For example, rapalogs increase AKT phosphorylation while suppressing mTORC1 function.…”
Section: Mirna and Pi3 Kinase Signaling In Hematopoietic Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovering the mTORC2 mechanism has important ramifications for the use of mTOR inhibitors in the clinic for cancer: these inhibitors will prevent the phosphorylation of PKC and cause its loss, compromising the utility of these drugs (Sun, 2021). However, elucidation of the function of mTORC2 in relieving PKC dimerization unveils a potential approach to desensitize PKC to mTOR inhibitors.…”
Section: Therapeutic Implications For Novel Agc Activation Mechanismsmentioning
confidence: 99%
“…With the gradual deepening of understanding, it had been found that there were feedbacks of multiple kinases during the employment of Everolimus, such as hyperphosphorylation of eIF4E at the Ser209 site, which led to the development of drug resistance 15 . The mTOR inhibitor Rapalog induced eIF4E phosphorylation was done by kinases termed MAP kinase-interacting kinases (Mnks) independently of the conventional Mnk-activating MAPK pathway 16 .…”
Section: Loss Of Intracellular Mir-7-5p Induces Phosphorylation Of Mnk/eif4e Axis But Supplement Of Extra Exosomal Mir-7-5p Can Reverse Imentioning
confidence: 99%